2000
DOI: 10.1136/heart.84.4.355
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis: a pivotal event or an epiphenomenon in the pathophysiology of heart failure?

Abstract: EditorialApoptosis: a pivotal event or an epiphenomenon in the pathophysiology of heart failure?Apoptosis, or programmed cell death, is an evolutionary conserved genetically programmed process by which multicellular organisms regulate cell numbers. It is critical in development and in tissue homeostasis. Unlike necrosis, the process is active, energy requiring and precisely regulated. Apoptosis in cardiac development and diseaseCardiac myocytes are by and large terminally diVerentiated and have a limited capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Activation of caspase-3 is mediated by multiple pathways, simply divided into mitochondria-dependent and -independent pathways (24,25,30). In the present study, the mitochondria-dependent pathway was examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of caspase-3 is mediated by multiple pathways, simply divided into mitochondria-dependent and -independent pathways (24,25,30). In the present study, the mitochondria-dependent pathway was examined.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-3 plays a pivotal role in the execution of apoptosis (24,30). Cells deficient in caspase-3 were resistant to apoptosis (31).…”
Section: Discussionmentioning
confidence: 99%
“…78). In either instance, reduction in apoptosis to basal levels might ultimately be of benefit to patients, although it has been argued that a complete elimination of apoptosis might not be advantageous in the long term (79), as it could result in neoplasia and/or autoimmunity complications.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis, or programmed cell death, is evident in the myocardium of subjects with end‐stage HF who undergo cardiac transplantation, 7,8 and the resultant loss of cardiac myocytes contributes to HF progression 9,10 . The apoptotic program is triggered by the activation of Fas, a transmembrane receptor belonging to the TNF receptor superfamily 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown elevated myocardial TNF‐α, interleukin (IL)‐1β, FasL, and IL‐6 15–19 . Cytokines have been proposed to play an important role in the remodeling of the myocardium and may facilitate apoptosis and HF progression 10,11 . In myocardial cells, the apoptotic signal is transmitted to the IL‐1β‐converting enzyme (ICE) like protease effector cascade by a cytosolic complex of activated Fas with Fas‐associated death domain (FADD) protein and FADD‐like ICE (FLICE) 2 …”
Section: Introductionmentioning
confidence: 99%